Ranking and mapping the high conservation priority bird species of Saudi Arabia - Christopher R. J. Boland (Resilience Alliance, 2020)
One of the challenges facing conservation biologists and land managers is to determine which species in the biota should receive conservation priority. This is particularly challenging in regions with comparatively little baseline ecological data, such as the Arabian Peninsula. Here we create a list of high conservation priority species for the birds of Saudi Arabia using objective criteria. In total, 102 of Saudi Arabia's 401 regularly occurring bird species were assigned as high conservation priority. We then rank the conservation priority of these species based on their threatened status, population trend, national distribution and abundance, level of national responsibility, endemicity, and evolutionary distinctiveness. We use GIS to map the locations of high conservation priority species, revealing that most occur in the Kingdom's southwest (in the Asir Mountains and foothills, Tihama coastal plains, and Red Sea coastline). A wide array of threats is impacting Saudi Arabia's highest conservation priority birds, particularly overhunting, alpine habitat fragmentation and degradation, Allee effects, secondary poisoning, and persecution. The methodology that we developed could be easily applied to other taxa and in other countries to help identify and rank high conservation species in other regions with limited baseline data.